Inventory of inshore Polychaetes from the Romanian coast (Black Sea) - SURUGIU, V. (Mediterranean Marine Science, 2005)
A survey conducted in inshore waters along the Romanian coast of the Black Sea from 1994 to 2000, yielded 24 polychaete species belonging to 10 families as follows: Polynoidae (2), Phyllodocidae (2), Syllidae (3), Nereididae (5), Spionidae (5), Capitellidae (3), Nerillidae (1), Sabellidae (1), Serpulidae (1), and Spirorbidae (1). Polydora websteri (Hartman, 1943) is a new record for the Mediterranean and Black Sea region. P. cornuta (Bose, 1802) is first recorded in the Black Sea. Additionally, two other species, namely Harmothoe imbricata (Linnaeus, 1767) and Typosyllis hyalina (Grube, 1863), are new to the Romanian fauna. The systematic position of some species is discussed. The information on geographical distribution within the Mediterranean region of species found is also provided.